The Influence Of Digital Marketing On Customers' Interest In Bank Bengkulu, Padang Ulak Tanding Branch - Rizki, Muhammad Gilang; Irwanto, Tito; Febliansa , Muhammad Rahman (Utami Publisher, 2025)
The tight competition in the banking industry requires banks to make various efforts to attract customers to use their products. One of the factors that influences customer interest is digital marketing. The purpose of this study is to determine the effect of digital marketing on customer interest in Bank Bengkulu, Padang Ulak Tanding Branch.This research method uses a quantitative descriptive research type. This research was conducted at Bank Bengkulu, Padang Ulak Tanding Branch. The sample in this study was 100 people with the sampling technique in this study being accidental sampling. Data collection techniques are observation, questionnaires and documentation. The data analysis technique used in this study is quantitative descriptive.The results of the study showed that there was a significant influence between digital marketing on customer interest with a t-value of 4.875> 1.66055 and a sig a value = 0.000 <0.050. The R2 value of 0.195 indicates that 19.5% of customer interest is influenced by digital marketing, the rest is influenced by other factors.